Why Has Inflation in the United States Remained So Low? : Reassessing the Importance of Labor Costs and the Price of Imports - Chan-Lau, Jorge (IMF Working Papers; Working Paper, 1999)
This paper examines some of the factors that have been influential in keeping inflation low in the United States during 1995-98, despite strong growth and high levels of employment. Our results identify three important variables: declines in import prices, a slowdown in the growth of nonwage labor compensation, and a decline in labor costs. We also reassess the role of labor costs and import prices in determining price inflation.